Pengaruh Pengetahuan Mahasiswa Akuntansi Tentang Pajak dan Audit Terhadap Minat Berkarir di Bidang Audit Dan Pajak - Wijoyo, Amin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Accounting students' knowledge about taxes and Auditing as an independent variable on interest in a career in taxation and Auditing as a dependent variable among accounting students in Jakarta. This research was conducted to evaluate accounting students' career interests in the field of tax and audit. Data taken from accounting student questionnaires. Data taken from all active accounting students at several campuses in Jakarta. The model used in this research is Microsoft Excel software and processed using the PLS program.